2006
DOI: 10.1056/nejmoa054915
|View full text |Cite
|
Sign up to set email alerts
|

Language Ability after Early Detection of Permanent Childhood Hearing Impairment

Abstract: Early detection of childhood hearing impairment was associated with higher scores for language but not for speech in midchildhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
329
7
16

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 424 publications
(368 citation statements)
references
References 19 publications
13
329
7
16
Order By: Relevance
“…[14][15][16] For example, in a mixed group of 7-to 9-year-old children with moderate to profound PCHI, we reported significantly higher receptive and expressive language scores in children whose PCHI was confirmed by 9 months compared with those with later-confirmed hearing loss. 17 Others have reported that children with PCHI aged under 6 years increased their narrative abilities over time after cochlear implantation. 18 In this report, we present a detailed analysis of our audiotaped expressive language data from a population of children with PCHI, half of whom had been exposed to UNHS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] For example, in a mixed group of 7-to 9-year-old children with moderate to profound PCHI, we reported significantly higher receptive and expressive language scores in children whose PCHI was confirmed by 9 months compared with those with later-confirmed hearing loss. 17 Others have reported that children with PCHI aged under 6 years increased their narrative abilities over time after cochlear implantation. 18 In this report, we present a detailed analysis of our audiotaped expressive language data from a population of children with PCHI, half of whom had been exposed to UNHS.…”
mentioning
confidence: 99%
“…Participants were similar to non-participants with respect to age, sex, and severity of hearing loss. 17 Twenty-three of these 120 were either non-verbal or used British Sign Language as their first language (Table II). Audio recordings of the completed Bus Story assessment were available in 89 of the 97 participants with PCHI whose first preference was to use oral language, with or without sign language, and in all 63 children in the comparison group with normal hearing.…”
mentioning
confidence: 99%
“…For comparisons within the group of teenagers with PCHL, we used norms obtained from the HCG (Kennedy et al., 2006). The group mean score and standard deviation scores for the HCG on each measure were used to derive age‐adjusted z scores for the teenagers with PCHL on that measure.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown in this sample that those with PCHL had mean reading levels significantly below those of the hearing comparison group (HCG) at both age groups 6–10 years (McCann et al., 2009) and 13–20 years (Pimperton et al., 2016). Similar findings have also been reported for language comprehension scores (Kennedy et al., 2006; Pimperton et al., 2017). Reading deficits for teenagers with PCHL were most severe in the domain of comprehension (Pimperton et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While the impact of undernutrition on cognitive and psychosocial development as well as educational attainment is well documented (6,7) , limited evidence still exists on the relationship between undernutrition and communication disorders in young infants, in sharp contrast with other sensory disabilities such as visual impairment which has been extensively linked with vitamin A deficiency (1) . Yet, such evidence is crucial for achieving optimal developmental outcomes in infants with CESHL, as effective intervention may be limited to the first year of life (8,9) . For instance, in line with the resolution of the World Health Assembly urging for early hearing detection programmes for infants (10) , the Joint Committee on Infant Hearing recommends that CESHL be detected by the age of 3 months to facilitate enrolment in appropriate family-oriented intervention ideally by the age of 6 months (4) .…”
mentioning
confidence: 99%